Boron bridged NiN4B2Cx single-atom catalyst for superior electrochemical CO2 reduction. (April 2022) - Gu, Xiaokang; Jiao, Yuying; Wei, Bo; Xu, Tengfei; Zhai, Pengbo; Wei, Yi; Zuo, Jinghan; Liu, Wei; Chen, Qian; Yang, Zhilin; Zhao, Feifei; Wang, Xingguo; et al.
Graphical abstract: Abstract: Single-atom nickel catalysts hold great promise in the application of electrocatalytic carbon dioxide reduction reaction (CO2 RR), but suffer from the sluggish kinetics and serious competitive hydrogen evolution reaction (HER), which restrict their overall catalytic performance. Herein, we report a boron-bridging strategy to manipulate the atomic coordination structure and construct a single-atom nickel catalyst with an active center of NiN4 B2 to realize excellent CO2 RR performance. Density functional theory analysis suggests that the unique NiN4 B2 sites with tuned electronic structure facilitate the adsorption of CO2 molecules and effectively suppress the HER pathway by increasing corresponding energy barrier. As-obtained Ni-SAs@BNC catalyst with a NiN4 B2 structure exhibits significantly enhanced catalytic activity and selectivity than commonly used single-atom nickel catalysts with a NiN4 structure, especially at high applied potentials. A high current density of up to (214 ± 21) mA cm −2 at a potential of −1.2 V with a high CO Faraday efficiency (FECO ) of ∼97% was achieved in a flow cell. This work inspires new insights into the rational design of atomic coordination structure of single-atom catalysts with tunable electronic structure for superior electrocatalytic activities.